2014
DOI: 10.1007/s00259-013-2671-9
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of HIV-associated lymphoma from HIV-associated reactive adenopathy using quantitative FDG PET and symmetry

Abstract: Purpose To determine the diagnostic accuracy of a semiautomated 18F-FDG PET/CT measurement of total lesion glycolysis (TLG), maximum and peak standardized uptake value at lean body mass (SUL-Max and SUL-Peak), qualitative estimates of left/right nodal symmetry and FDG uptake for differentiating lymphoma from reactive adenopathy in HIV-infected patients. Methods We retrospectively analyzed 41 whole-body 18F-FDG PET/CT studies performed in HIV-infected patients for clinical reasons. The study received institut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
45
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(49 citation statements)
references
References 27 publications
4
45
0
Order By: Relevance
“…As iPET has low or variable reported positive predictive value in DLBCL, this would be useful to investigate in future studies. Quantification of changes in tumour FDG using % reduction in SUV max values or other functional markers such as total lesion glycolysis and metabolic tumour volume may be necessary to optimize the prognostic performance of iPET, particularly in DLBCL [3335], and may help reduce false-positive findings relative to visual assessment alone. This was not assessed in our study, as uptake times for all scans were not strictly controlled.…”
Section: Discussionmentioning
confidence: 99%
“…As iPET has low or variable reported positive predictive value in DLBCL, this would be useful to investigate in future studies. Quantification of changes in tumour FDG using % reduction in SUV max values or other functional markers such as total lesion glycolysis and metabolic tumour volume may be necessary to optimize the prognostic performance of iPET, particularly in DLBCL [3335], and may help reduce false-positive findings relative to visual assessment alone. This was not assessed in our study, as uptake times for all scans were not strictly controlled.…”
Section: Discussionmentioning
confidence: 99%
“…16,18,34 In past years, other quantitative approaches, including metabolic tumor volume and total lesion glycolysis for [ 18 F] FDG-PET evaluations, have been investigated for differentiation of HIV-associated lymphoma from HIV-associated reactive adenopathy. 35,36 CT texture features can also be obtained from the same [ 18 F] FDG-PET/CT study. The combination model based on these quantitative PET metabolic metrics, CT texture parameters, and clinical parameters may need to be further evaluated in a future study for patients with head and neck squamous cell carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…& Liu found that a coexistent FDG avid nasopharyngeal lesion and generalized lymphadenopathy on PET/CT imaging is indicative of a malignant lymphoma rather than benign lymphoproliferative disease or nasopharyngeal carcinoma [10]. However, Mhlanga et al [1] found no significant difference in the nasopharyngeal region mean SUL-Max scores between patients with HIV-associated lymphoma and those with HIV-reactive adenopathy.…”
mentioning
confidence: 99%
“…In this issue of the European Journal of Nuclear Medicine and Molecular Imaging, Mhlanga et al [1] address the important challenge of differentiating between HIV-reactive lymphadenopathy and HIV-associated lymphoma using FDG PET/CT. What is more interesting about this study is the fact they rigorously assessed the quantitative PET metabolic metrics to distinguish these entities.…”
mentioning
confidence: 99%
See 1 more Smart Citation